Maternal near miss and quality of maternal health care in Baghdad, Iraq - Jabir Maysoon; Abdul-Salam Imad; Suheil Dhikra M; Al-Hilli Wafa; Abul-Hassan Sana; Al-Zuheiri Amal; Al-Ba'aj Rasha; Dekan Abeer; Tunçalp Özge; Souza Joao Paulo (BMC, 2013)
Abstract Background The maternal near-miss concept has been developed as an instrument for assisting health systems to evaluate and improve their quality of care. Our study aimed at studying the characteristics and quality of care provided to women with severe complications in Baghdad through the use of the World Health Organization (WHO) near-miss approach for maternal health. Methods This is a facility-based, cross-sectional study conducted in 6 public hospitals in Baghdad between March 1, 2010 and the June 30, 2010. WHO near-miss approach was utilized to analyze the data in terms of indicators of maternal near miss and access to and quality of maternal care. Results The maternal near-miss rate was low at 5.06 per 1,000 live births, while the overall maternal near miss: mortality ratio was 9:1. One third of the near-miss cases were referred from other facilities and the mortality index was the same for referred women and for in-hospital women (11%). The intensive care unit (ICU) admission rate was 37% for women with severe maternal outcomes (SMO), while the overall admission rate was 0.28%. Anemia (55%) and previous cesarean section (45%) were the most common associated conditions with severe maternal morbidity. The use of magnesium sulfate for treatment of eclampsia, oxytocin for prevention and treatment of postpartum hemorrhage, prophylactic antibiotics during caesarean section, and corticosteroids for inducing fetal lung maturation in preterm birth is suboptimum. Conclusions The WHO near-miss approach allowed systematic identification of the roadblocks to improve quality of care and then monitoring the progress. Critical evidence-based practices, relevant to the management of women experiencing life-threatening conditions, are underused. In addition, possible limitations in the referral system result in a very high proportion of women presenting at the hospital already in a severe health condition (i.e. with organ dysfunction). A shortage of ICU beds leading to women taken care of without admission to ICU may also contribute to a high proportion of maternal deaths and organ dysfunction.